Carbon Credits and Crude Oil: An Investigation of the Price Returns Interaction in the International Market - André Assis de Salles; Renato Barros Lima (Naše gospodarstvo/Our economy, 2024)
This paper aims to verify the relationship between the international markets for crude oil and carbon credits. We studied the returns of prices practiced in these markets, focusing on the transmission of shocks between oil prices and carbon credit prices. The methodological approach used financial econometrics to study these variables' risk and return relationships. Besides causality and cointegration hypothesis tests, the VECM and GARCH models were estimates. There is a shortand long-term interaction between these variables. The volatility models show a significant association between the volatilities of the two variables of interest. Fossil fuels, mainly crude oil, generate energy that has substantial restrictions. At the same time, the carbon credits market has shown significant growth that can contribute to the use of energy from fossil fuels with parsimony and responsibility. Studying these variables and their interactions contributes to understanding the importance of the carbon market.